SCN8A heterozygous variants are associated with anoxic‐epileptic seizures. Issue 5 (10th February 2020) - Ranza, Emmanuelle; Z'Graggen, Werner; Lidgren, Mathias; Beghetti, Maurice; Guipponi, Michel; Antonarakis, Stylianos E.; Absoud, Michael; Goyal, Sushma; Pal, Deb K.; Korff, Christian M.
Abstract: Anoxic‐epileptic seizures (AES) are rare outcomes of common childhood reflex anoxic syncope that trigger a true epileptic seizure. The term AES was coined by Stephenson in 1983, to differentiate these events from convulsive syncopes and the more common reflex anoxic syncopes. A genetic susceptibility for AES has been postulated; but, its molecular basis has up to now been elusive. We report here two illustrative cases and show the association of de novo SCN8A variants and AES. One of them had focal or generalized seizures and autonomic symptoms triggered by orthostatism; the second had breath‐holding spells triggered by pain or exercise leading to tonic–clonic seizures; both had repeatedly normal EEGs and a family history of reflex syncope. The data of three additional AES patients further suggest, for the first time, a link between SCN8A pathogenic variants and AES. The neurodevelopment of four patients was abnormal. Four of the five SCN8A mutations observed here were previously described in patients with seizure disorders. Seizures responded particularly well to sodium channel blockers. Our observation enriches the spectrum of seizures linked with SCN8A pathogenic variants.